Recent Advances in Minimally Invasive General Surgery A Retrospective Study - Muhammad Shah; Muhammad Iftikhar; Jamshed Alam; Rashid Aslam; Shimee Shahzadi (Gandhara University, 2023)
OBJECTIVES To evaluate the outcomes of minimally invasive general surgery (MIGS) and determine the indications for MIGS and its success rate. METHODS This retrospective study was conducted at the surgery unit of Hayatabad Medical Complex (HMC) Hospital, Peshawar, from January 2021 to December 2022. All the 200 patients who underwent MIGS were included in the study. Data regarding demographic characteristics, clinical presentation, type of MIGS, and intraoperative and postoperative complications were collected from the medical records and analyzed. The outcome of the study was assessed based on the success rate of the MIGS procedure and the occurrence of any postoperative complications. RESULTS The mean age of the patients was 43.3 years (range 10-75 years). The most common indication for MIGS was cholecystectomy (33.5%). Other indications included appendectomy (17.5%), hernia repair (12%), small bowel resection (10%), and gastrectomy (7%). The overall success rate of MIGS was 97.5%. The most common postoperative complication was wound infection (6.5%). There were no deaths due to MIGS. CONCLUSION The study findings suggest that MIGS is a safe and effective procedure for managing various surgical diseases and can be performed with minimal morbidity and mortality. Further randomized controlled trials are needed to confirm the safety and efficacy of MIGS in different settings.